(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Psychosis, a chronic mental illness, can be treated with plants and traditional herbs, which contain phytochemicals and counter oxidants to support body organs and reduce schizophrenia risk. The study aimed to evaluate the anti-psychotic potential of Bergenia ciliata by collecting, authenticating, and preparing a methanolic extract from its roots. Two experimental models were used to simulate psychotic symptoms in rats and assess the extract's influence on movement and activity patterns. The objective parameters included behavioral assessments of stereotypic and locomotor activities to quantify the effects of the extract. Biochemical analysis was conducted on brain tissue homogenates, focusing on glutathione (GSH) estimation, acetylcholinesterase (AchE) activity assay, and TNF-α measurement to evaluate inflammation levels. Histopathological analysis of the brain, particularly the frontal cortex and hippocampus, was also conducted to examine structural changes in brain tissues. Key observations: This analysis provided insights into the neuroprotective effects of the methanolic root extract on critical brain regions implicated in psychotic disorders. The results showed that the apomorphine control group had high stereotypy levels, while the apomorphine + standard drug group showed a significant reduction in stereotypy scores at 60 and 90 minutes. Both dosages of Bergenia ciliata showed significant reductions in stereotypy scores at 60 and 90 minutes, suggesting its potential in mitigating the stereotypy induced by apomorphine. The study also found significant differences in GSH, AchE, and TNF-alpha levels between the normal control (vehicle) and Apomorphine 1.5 mg/kg, the std drug (Haloperidol 1 mg/kg), and Bergenia ciliata (250 and 500 mg/kg). Recordings in an Actophotometer were taken on Days 1, 8, 15, and 23. The data revealed no significant differences between groups, except for the positive control, this exhibited a significant decrease in comparison to the healthy animals, a notable increase in locomotor activity was observed following the administration of diazepam in the B. ciliata group, particularly when contrasted with the positive control group. Additionally, B. ciliata exhibited significant effects on biochemical parameters compared to the positive control. The histology of the brain's cerebellar cortex, hippocampus, and frontal cortex under different conditions showed well-preserved layers and healthy neurons. Diazepam-treated brain showed mild neuronal degeneration with vacuolations and congested blood vessels. Oligodendrocytes and pyramidal cells were less affected, but some neuronal degeneration was evident. Both low and high doses of the test drug maintained normal cortical and hippocampal structure, with healthy neuronal architecture, oligodendrocyte presence, and adequate vascularization. The study suggests that Bergenia ciliata may be an effective anti-psychotic agent, potentially reducing inflammation and enhancing psychotropic effects.